Investigation of the Impact of the Wafer Resistivities on Double-Side Passivated Contact Silicon Solar Cells - Pradeep Padhamnath; Gabby De Luna; Ruohan Zhong; John Derek Arcebal; Ajeet Rohatgi; Armin G. Aberle (SiliconPV Conference Proceedings)
In this work, we investigate the impact of substrate resistivities on the performance of poly-Si based double-side passivated contact solar cells, featuring high-temperature fire-through contacts to both n-type and p-type poly-Si, where the contacts are co-fired at the same firing temperatures. Large-area double-side passivated contact solar cells are fabricated on n-type wafers and thoroughly characterized to understand the impact of the change in Si wafer resistivity on the performance of the solar cells. The solar cells are fabricated on n-type substrates, with p+ poly-Si deposited on the planar rear side and n+ poly-Si on the textured front. The n+ poly-Si on the front side is selectively patterned to constrain it to the regions below the metal contacts. The fabricated solar cells achieve ≈ 22% efficiency on large area using high-temperature fire-through metallization. With the help of detailed characterization, we identify the losses that limit the device efficiency.